Current Progress and Challenges in the Development of a Hepatitis C Virus Vaccine - Thomas F. Baumert (Frontiers Research Topics, 2019)
More than 70 million people worldwide are infected with hepatitis C virus, a major cause of liver cirrhosis, liver failure and hepatocellular carcinoma world-wide. In the last decade, this cancer has emerged as the second leading cause of cancer death and the global burden is increasing by two million new infections per year, mainly due to injection drug use. An effective vaccine will be the most effective means to contain the spread of this virus worldwide. The articles in this Research Topic describe the progress that has been made towards a preventive vaccine and the challenges that still need to be overcome to ultimately achieve this goal.